Burned : a Vanessa Pierson novel - Wilson, Valerie Plame; Lovett, Sarah, 1953- (2014)
Believing that a nuclear arms dealer she has pursued throughout her career is behind a series of terrorist incidents, covert CIA ops officer Vanessa Pierson is contacted by her target, who claims that a government insider is actually responsible.
Keywords: Women intelligence officers -- Fiction; Undercover operations -- Fiction; Suspense fiction; Spy stories